2021
DOI: 10.1063/5.0051093
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin 2D-oxides: A perspective on fabrication, structure, defect, transport, electron, and phonon properties

Abstract: for electronic devices. Oxides constitute a broad family of materials with a wide range of potential applications, from catalysis to electronic, photonic, ferroelectric, magnetic and multiferroic functionalities. Understanding structure-property relations in free-standing, supported, and confined two-dimensional ceramics or "ceramic flatlands" has been identified as one of the challenges for future work in ceramics by a recent National Science Foundation workshop. [9] Nonetheless, over the last decade, there h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 210 publications
1
14
0
Order By: Relevance
“…A comparison between the bulk α-MoO 3 powder Raman spectra and those of some representative exfoliated samples is reported in Figure S1 of the Supporting Information (SI). In these spectra, the signals at 996 and 666 cm –1 and at wavenumbers <400 cm –1 show a slight red shift following dimensional reduction, which could be however within the Raman error, although it has been theoretically predicted (the attribution of the signals to the different Raman modes is clarified in Table S1). Normalization on the most intense symmetric stretching mode of the terminal oxygen atoms or the doubly connected bridge–oxygen Mo–O–Mo at 818 cm –1 does not also highlight any change in relative intensity ratios with other modes, thus confirming that Raman for this specific layered material is not the suitable technique to ascertain the dimensional reduction, as it was shown before. , …”
Section: Results and Discussionsupporting
confidence: 61%
“…A comparison between the bulk α-MoO 3 powder Raman spectra and those of some representative exfoliated samples is reported in Figure S1 of the Supporting Information (SI). In these spectra, the signals at 996 and 666 cm –1 and at wavenumbers <400 cm –1 show a slight red shift following dimensional reduction, which could be however within the Raman error, although it has been theoretically predicted (the attribution of the signals to the different Raman modes is clarified in Table S1). Normalization on the most intense symmetric stretching mode of the terminal oxygen atoms or the doubly connected bridge–oxygen Mo–O–Mo at 818 cm –1 does not also highlight any change in relative intensity ratios with other modes, thus confirming that Raman for this specific layered material is not the suitable technique to ascertain the dimensional reduction, as it was shown before. , …”
Section: Results and Discussionsupporting
confidence: 61%
“…In conclusion, we have shown that excitons in flat band materials may have intriguing properties which contradict textbook expectations. Flat bands correspond to localized electronic states, and as one would expect, the exciton binding energy is in general very large 34 . However, when the single-particle excitations that are mixed to form an exciton are charge transfer excitations with a mirror symmetry, the exciton wavefunction delocalizes.…”
Section: /14 3 Discussionmentioning
confidence: 78%
“…15, on the basis of a model by Bechstedt et al 31 , the self-energy was rescaled by a factor 0.38 improving the agreement of the onset energy with ellipsometry data 32 . Later work showed that the effect was largely overestimated and that it should rather reduce the gap by an amount of the order of 0.2 eV, way too small to account for the gap overestimate 33,34 . While the formation of self-trapped electron polarons has been found to be important in V 2 O 5 [35][36][37] , they are not expected to occur at the time scale of an optical absorption and can thus not explain the discrepancy.…”
Section: Introductionmentioning
confidence: 98%
“…, lithium cobalt oxide (LCO), and are a relatively understudied class of 2D particle surfactants but of great interest for potential catalytic, electrochemical, and superconductive properties. 32–39 Limited studies have reported the use of cobalt oxide materials in emulsions. One example is the use of oil-in-water (o/w) Pickering emulsions to prepare composites of LCO nanoparticles and polyaniline as the positive electrode in a lithium battery; the discontinuous phase of the emulsion was aniline dissolved in toluene and LCO particles served as surfactant.…”
Section: Introductionmentioning
confidence: 99%